Techniques de consciences du corps énergétiques et poétiques - Marceau Chenault (Appareil)
This paper investigates the metaphor used in some of practices observed at the Shanghai Qigong medical research Institute. The analogic images mentioned during the teaching-learning guide the perceptions towards aesthetics space of the body animate with qi-breathing. It brings meaning to body awareness techniques composed of gestures adjustment, breathing regulation and guided attentions. With the references of Richard Shusterman works about the somaesthetic, we are addressing this embodied aesthetic of qi-breathing between somatic perceptions and body consciousness with various cultural interpretations, and its contemporary flow between health experiential knowledge, somatic teaching learning and artistic training. Qi-breathing aesthetics emerges from a technique and experiential “appareillage” filled with images, body schemas and interior visions: it flows between practicians, researchers, and artists within the globalization of the aesthetics of the soma.